Asthma and Allergic Rhinitis in Quebec Children - Benoît Lévesque; Marc Rhainds; Pierre Ernst; Anne-Marie Grenier; Tom Kosatsky; Nathalie Audet; Pierre Lajoie (Canadian Respiratory Journal)
BACKGROUND: The Health and Social Survey of Quebec Children and Youth, conducted on representative samples of children nine, 13 and 16 years of age, provided data on the prevalence and determinants of asthma and allergic rhinitis in Quebec.